OPALE: Operational assessment of landscape water eco-functionalities. (February 2022) - Trévisan, D.; Taillandier, P.; Sarrazin, B.; Etienne, D.; Ayari, N.; Petiqueux, C.; Quétin, P.; Janin, C.
Abstract: The present article proposes a suite of programs aimed at (i) representing landscape organization in relation with the functioning of annual crops or breeding systems, (ii) evaluating water movements from biomass and hydrological exchanges, and (iii) analyzing the transfer dynamics of nutrients, suspended matter or fecal bacteria based on particle tracking methods. Simulations provided indications about the underlying processes that drive exchanges and sink-source effects operating at the landscape scale. OPALE was tested in three agricultural contexts and biophysical situations. Water flows and flows of associated matters were compared to data recorded at the catchment outlet, and showed the efficiency of the algorithms developed in the generic OPALE libraries. This article describes the underlying hypotheses and the full mathematical framework and procedures used to assess landscape eco-functionality. Several examples are given to illustrate the use of OPALE in landscape reconfiguration prospects (e.g. influence of landscape composition and structure on plant transpiration, stream flow, erosion, nutrient and organism fluxes in water) for the agroecological transition. Highlights: OPALE is a suite of programs for the representation and analysis of landscapes in arable crops and grasslands conditions. OPALE allows for efficient evaluation of water and matter outflows (nutrient, suspended matter and fecal bacteria). OPALE leads to computed indicators to assess landscape functioning and water-related eco-functionality in various conditions.